7p-6p=-11

Simple and best practice solution for 7p-6p=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7p-6p=-11 equation:


Simplifying
7p + -6p = -11

Combine like terms: 7p + -6p = 1p
1p = -11

Solving
1p = -11

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Divide each side by '1'.
p = -11

Simplifying
p = -11

See similar equations:

| Y=0.25x^2+10x+80 | | 3x^(-1/2)=8 | | 12-v=9 | | 4x+5x-34=68-8x | | 3x^(-1/2)-8=0 | | (a*a)-5a+25+(b*b)+6b+36=0 | | -6=3(x-19) | | 4x+x-15+x-4=180 | | 6-2x=6x-10x-16 | | 5b+6b-9b+1=7 | | 2(1-2a)=7(a-6) | | 2(x-3)-3=3 | | 11=4(n-17)+15 | | 7-z=-3 | | 12x+24y=60 | | ((4y^4/3x^4y^7))^3 | | 4s-3s=15 | | 8a^4=9a^2 | | 1/2:1/2 | | (a*a)-5a+25+(b*b)+6b+61=0 | | 11x+-9x-3=-9 | | G(x)=f(x+3)+1 | | (4y^4/3x^4y^7)^3 | | 11x+-9r-3=-9 | | c+x^2+40x=0 | | 13+x=y-17 | | -20x+5y=15 | | -5(r+7)=88 | | 2=4-6q | | 8-h=9 | | http://media.apexlearning.com/Images/200712/03/1536e7c5-c59f-4ae2-b5f1-51bc0e2ea368.gif | | 2(5+2x)=18+3 |

Equations solver categories